1972
DOI: 10.1071/bi9721313
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Total Entry Rate and Resynthesis of Glucose in Sheep Using Glucoses Uniformly Labelled With 14C and Variously Labelled With 3H

Abstract: Comparisons have been made of [6_ 3H]-, [3-3H]-, and [2-3H]glucose with [U-14C]glucose for measuring parameters of glucose metabolism in sheep given their daily ration in 24 equal amounts at hourly intervals. The specific radioactivity (R) of plasma glucose was measured at frequent intervals from 0 to 10 hr and 0 to 32 hr after the start of a constant infusion. or single injection, of mixtures of these isotopes respectively.Estimates of glucose pool size by consideration of either the initial rectilinear slope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

1975
1975
2003
2003

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(43 citation statements)
references
References 7 publications
6
37
0
Order By: Relevance
“…Use of these isotopes assumes that their metabolism reflects the metabolism of the carbon skeleton of glucose. This assumption is based primarily on studies in postabsorptive nondiabetic animals and man (3,5,6,(12)(13)(14)25 [6'4C]glucose in the diabetic patients, but were lower in the nondiabetic subjects. Both futile cycling and incorporation of radioactivity into and release from glycogen can alter isotopically determined glucose turnover rates (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of these isotopes assumes that their metabolism reflects the metabolism of the carbon skeleton of glucose. This assumption is based primarily on studies in postabsorptive nondiabetic animals and man (3,5,6,(12)(13)(14)25 [6'4C]glucose in the diabetic patients, but were lower in the nondiabetic subjects. Both futile cycling and incorporation of radioactivity into and release from glycogen can alter isotopically determined glucose turnover rates (16).…”
Section: Discussionmentioning
confidence: 99%
“…[23H]glucose also loses its label as part of the glucose/glucose-6-phosphate futile cycle (3,5,8,13). This results in an overestimate of glucose turnover rates in the postabsorptive state.…”
Section: Introductionmentioning
confidence: 98%
“…In these conditions, the irreversible glucose loss rate is the rate at which glucose leaves the sampled compartment never to return to that compartment, while the glucose entry rate is the rate of entry of glucose into the sampled compartment [56]. A combination of data from publications which compared different types of tracers [27,28,43] showed that on average glucose entry rates are 40% higher than the irreversible glucose loss rates.…”
Section: Methodological Aspectsmentioning
confidence: 99%
“…The tracer of choice for the study of glucose turnover per se is the irreversible [6-3 H] glucose [52]. The simultaneous use of [2-*H] and [U-*C] showed differences in glucose turnover of the order of 13-14% in sheep [48,56]. On the contrary, glucose turnover values were similar whether using [U- 14 C] or [6-3 H] labelled glucose [15,48].…”
Section: Methodological Aspectsmentioning
confidence: 99%
“…followed by a constant infusion of the remaining tracer over the ensuing 110 min. Utilization of this isotope has been noted to measure the least amount of recycling in tracer kinetic studies in rabbits and sheep (3,12). After a 60-min equilibration period following the priming dose, blood samples for plasma glucose, insulin, and glucose specific activity determination were obtained at 10-min intervals from 60-1 10 min and for plasma glucagon at…”
Section: Methodsmentioning
confidence: 99%